Drogas, valores sociales y neoliberalismo el debate en el área andina a partir de 1990 - Mansilla, H. C. F. (Nómadas. Critical Journal of Social and Juridical Science, 2008)
In the Andean area the coca / cocaine complex has won a significant economic and political weight. Because of that the discussion is not free of distorting factors, like political interests. The drug legalization, which is supported by an increasing number of known personalities, is akin to neoliberal philosophy and individualist morality. This position is also shared by postmodernist conceptions. What the coca producers really desire is something that they cannot openly utter: the maintenance of the present situation, which is characterized by a rhetorical condemnation and a legal prohibition and, at the same time, by the effective tolerance vis-a-vis the production and commercialization of coca and its by-products.
Keywords: Coca / cocaine; Drug legalization; Neoliberalism; Opium War; Prohibition Law; Public welfare